1989
DOI: 10.1212/wnl.39.4.498
|View full text |Cite
|
Sign up to set email alerts
|

Neurobrucellosis

Abstract: We report 13 patients with neurobrucellosis categorized into five groups: acute meningoencephalitis; papilledema and increased intracranial pressure, meningovascular, CNS demyelinization, and peripheral neuropathy. We treated the patients successfully, without relapse, with two or more antimicrobials: rifampicin, co-trimoxazole, and doxycycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 0 publications
2
98
0
6
Order By: Relevance
“…Meningitis has been reported to be the most frequent presentation, occurring in about 50% of the cases [13]. In our study, 16 cases (80%) had evidence of meningeal infection, as indicated by pleocytosis, elevated protein level in the CSF and usually hypoglycorrhachia.…”
Section: Discussionsupporting
confidence: 48%
“…Meningitis has been reported to be the most frequent presentation, occurring in about 50% of the cases [13]. In our study, 16 cases (80%) had evidence of meningeal infection, as indicated by pleocytosis, elevated protein level in the CSF and usually hypoglycorrhachia.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, the presentation of NB is diverse (6). The most common type of NB affecting the CNS is chronic meningoencephalitis in which lymphocytic pleocytosis and high protein levels are detected in the CSF (8). Because Brucella is a slow-growing bacterium, CSF and blood cultures can be negative, so the diagnosis is generally made by serological methods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, splenial T2-hyperintensity in our patient was thought to result from an alternative mechanism. CNS demyelination can be a rare feature of NB (6,(8)(9)(10). In 1963, Fincham et al reported that the white matter changes in NB were sequelae of demyelination, as confirmed by pathologic study (9).…”
Section: B Amentioning
confidence: 97%
“…Studies have demonstrated that 4-13% of patients have neurological involvement [5,6]. Neurological involvement has been reported in both the acute or chronic period of brucellosis.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological involvement has been reported in both the acute or chronic period of brucellosis. Central nervous system involvements of meningitis, meningoencephalitis, myelitis, arachnoiditis, brain abscess and epidural abscess may be presented [5][6][7]. Peripheral nervous system involvements of polyradiculoneuritis, cranial nerve neuropathies and peripheral neuropathies have been reported.…”
Section: Introductionmentioning
confidence: 99%